Like Fibrin, (DD)E, the Major Degradation Product of Crosslinked Fibrin, Protects Plasmin from Inhibition by α2-antiplasmin - Lee, Agnes Y. Y.; Fredenburgh, James C.; Stewart, Ronald J.; Rischke, Janice A.; Weitz, Jeffrey I. (Thrombosis and Haemostasis, 2001)
Plasmin generation is localized to the fibrin surface because tissue-type plasminogen activator (t-PA) and plasminogen bind to fibrin, an interaction that stimulates plasminogen activation over a hundred-fold. To ensure efficient fibrinolysis, plasmin bound to fibrin is protected from inhibition by α2-antiplasmin. (DD)E, a major soluble degradation product of cross-linked fibrin that is a potent stimulator of t-PA, compromises the fibrin-specificity of t-PA by promoting systemic activation of plasminogen. In this study we investigated whether (DD)E also protects plasmin from inhibition by α2-antiplasmin, facilitating degradation of this soluble t-PA effector. (DD)E and fibrin reduce the rate of plasmin inhibition by α2-antiplasmin by 5- and 10-fold, respectively. Kringle-dependent binding of plasmin to (DD)E and fibrin, with Kd values of 52 and 410 nM, respectively, contributes to the protective effect. When (DD)E is extensively degraded by plasmin, yielding uncomplexed fragment E and (DD), protection of plasmin from inhibition by α2-antiplasmin is attenuated. These studies indicate that (DD)E-bound plasmin, whose generation reflects the ability of (DD)E to stimulate plasminogen activation by t-PA, has the capacity to degrade (DD)E by virtue of its resistance to inhibition. This provides a mechanism to limit the concentration of (DD)E and maintain the fibrin-specificity of t-PA.
Keywords: Plasmin; α2-antiplasmin; fibrin; tissue-type plasminogen activator; (DD)E